Volume 5: 25th International Conference on Design Theory and Methodology; ASME 2013 Power Transmission and Gearing Conference 2013
DOI: 10.1115/detc2013-12913
|View full text |Cite
|
Sign up to set email alerts
|

Improving Overlapping Between Testing and Design in Engineering Product Development Processes

Abstract: Testing components, prototypes and products comprise essential, but time consuming activities throughout the product development process particularly for complex iteratively designed products. To reduce product development time, testing and design processes are often overlapped. A key research question is how this overlapping can be planned and managed to minimise risks and costs. The first part of this research study investigates how a case study company plans testing and design processes and how they manage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…This considered both descriptive and normative work as well as treatments of testing in design and development process models. Beginning with the reviews recently published in Tahera et al (2017) and Wynn and Clarkson (2018), the bibliographies of those articles were studied, relevant original sources were revisited and their bibliographies studied in turn. Google Scholar and Scopus were used to find additional relevant sources and key journals including Research in Engineering Design, Journal of Engineering Design, and IEEE Transactions on Engineering Management were considered.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This considered both descriptive and normative work as well as treatments of testing in design and development process models. Beginning with the reviews recently published in Tahera et al (2017) and Wynn and Clarkson (2018), the bibliographies of those articles were studied, relevant original sources were revisited and their bibliographies studied in turn. Google Scholar and Scopus were used to find additional relevant sources and key journals including Research in Engineering Design, Journal of Engineering Design, and IEEE Transactions on Engineering Management were considered.…”
Section: Methodsmentioning
confidence: 99%
“…From the point of view of testing, these process models are partial not only in the activities that they depict, but also in their structures which typically do not emphasise the relationships between design and testing. We argue that this is an important gap, because a number of researchers have reported that testing is a very significant cost factor in engineering design and development (Tahera et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations